The Role of AI and FoMO in Marketing Transformation in Driving Generation Z Shopping Decisions - Efendi, Nasrul; Lubis, Tya Wildana Hapsari; Hutagalung, Apni; Gultom, Cinta (Universitas Islam Kadiri, 2025)
This study examines how Artificial Intelligence (AI) and Fear of Missing Out (FoMO) contribute to changes in purchasing behavior among Generation Z. The study involved individuals aged 17 to 26 who actively use the Shopee platform. A total of 511 participants were recruited using convenience sampling, based on the Lemeshow formula for an unknown population size. Data analysis was conducted using SmartPLS 3, incorporating evaluation of convergent validity, Average Variance Extracted (AVE), discriminant validity, composite reliability, R-squared value, path significance, and effect size. The findings indicate that AI has a strong and statistically significant effect on purchasing decisions (f² = 0.813, p = 0.000), indicating its effectiveness in influencing Generation Z's online shopping behavior. In contrast, FoMO only showed a negligible and insignificant impact (f² = 0.018, p = 0.515), indicating limited empirical support for its role in shaping purchasing decisions.